INOVASI MODEL PEMBELAJARAN DI SD DALAM MENGHADAPI TANTANGAN KURIKULUM MERDEKA - El-Syifa Qolbi (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze innovative learning development models in elementary schools in addressing the challenges of implementing the Merdeka Curriculum. The Merdeka Curriculum emphasizes student-centered learning, character strengthening through the Pancasila Student Profile, and the development of literacy and numeracy competencies. In its implementation, several challenges arise, including teachers’ readiness to apply differentiated instruction, technology integration, and project-based learning.This research employs a qualitative approach using a library research method. Data were collected through the review of various written sources, including books, scientific journals, research articles, educational policy documents, and official Merdeka Curriculum modules. Data analysis was conducted through data reduction, classification, interpretation, and synthesis of relevant theories and previous research findings.The findings indicate that innovative learning models such as Project-Based Learning (PjBL), differentiated instruction, digital technology integration, and diagnostic and formative assessment are effective strategies in addressing the challenges of the Merdeka Curriculum. Adaptive, contextual, and student-centered learning models are essential in improving the quality of learning in elementary schools.